First description of Blastocystis sp. and Entamoeba sp. infecting zoo animals in the Qinghai-Tibetan plateau area, China - Qi, Tongsheng; Zheng, Wangli; Guo, Liangting; Sun, Yali; Li, Jixu; Kang, Ming (Frontiers in Cellular and Infection Microbiology, 2023)
Protozoan parasites are a well-known threat to human health, particularly for people working at or visiting zoos, and potentially cause zoonotic diseases in humans. Captive wildlife may be potential reservoirs for human infection with protozoan parasites. Therefore, focusing on zoonotic protozoan infections in zoo animals is critical. However, there is no report on this topic in the Qinghai-Tibetan Plateau region. In this study, a total of 167 and 103 fecal samples were collected from 12 animal species from Qinghai-Tibet Plateau Wildlife Park in winter and summer, respectively, to detection the prevalence of infections and subtype distribution with Entamoeba sp., Cryptosporidium sp., Giardia duodenalis, Enteromicrosporidia bieneusi sp., Blastocystis sp. by PCR assay. The results showed that a total of 21 fecal samples collected in winter, including from 2 white-lipped deer, 8 Sika deer, 6 blue sheep, 2 wolves and 3 bears, were positive for Entamoeba, with a 12.6% (21/167) positive rate. However, 4.9% (5/103) of animals in summer were positive for Entamoeba, including 1 snow leopard, 1 tiger, 1 Tibetan argali and 2 mouflon. Moreover, 1 white-lipped deer and 1 bear were found to be positive for Blastocystis sp., one zoonotic STs (ST10) was identified and found in white-lipped deer. We found no effect on season on Blastocystis sp. and Entamoeba sp. colonization. To the best of our knowledge, this study is the first description of Blastocystis sp. and Entamoeba sp. infecting zoo animals in the plateau area. The findings provide the latest data on Entamoeba sp. and Blastocystis sp. in zoo animals in China.